Os usos e os atravessamentos do cineclube (e do cinema) na tessitura dos currículos em redes nos cotidianos - Cazé, Bárbara Maia Cerqueira (2015)
This study inquires on usages and crossings of film society (and cinema) on the fabrics of network curriculum in the everyday life of a state managed public high school in Espírito Santo. We adopt theoretical-methodological references such as researches in/ of/ with everyday life (ALVES, 2008a, 2008b; FERRAÇO, 2002, 2003; OLIVEIRA, 2012), in a intense exercise of living, hearing, feeling tastes and smells, experiencing the dynamics of the fabrics of everyday life networks in which all of us are involved. A research that was not defined a priori, on the contrary, it has woven within itineraries, curves, stumblings, vicissitudes and the interlacing of networks. Production of research data was based on conversation (LARROSA, 2003; CERTEAU, 1994) produced after cinema sessions at film society Nome Provisório, from June to December 2014. We have attended to the projections of the films: Narradores de Javé, Quanto vale ou é por quilo?, Madame satã, O veneno está na mesa e Raspage; and we left ourselves intertwine throughout the fabrics of curriculum and the several lines that go along with the school. We concluded that film society operates as a profitable space-time of learning and, mostly, an important dimension of dialogue and community gathering.